2012
DOI: 10.1002/eqe.2235
|View full text |Cite
|
Sign up to set email alerts
|

A frequency response function change method for damage localization and quantification in a shear building under ground excitation

Abstract: A frequency response function change (FRFC) method to detect damage location and extent based on the change in the frequency response functions of a shear building under the effects of ground excitation was proposed in this paper. The damage identification equation was derived from the motion equations of the system before and after the occurrence of the damage. Efforts to make the FRFC method less model‐dependent were made. Intact system matrices, which could be estimated using the measured data without the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It is shown that the uncertainty due to nonlinear effects is hardly comprehensible in comparison with other measurement uncertainties in dynamic experiments . Some researchers developed damage detection methods with the assumption of linear elastic behavior under small ground excitations . Limongelli validated the Interpolation Damage Detecting Method neglecting the effect of nonlinear behavior .…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that the uncertainty due to nonlinear effects is hardly comprehensible in comparison with other measurement uncertainties in dynamic experiments . Some researchers developed damage detection methods with the assumption of linear elastic behavior under small ground excitations . Limongelli validated the Interpolation Damage Detecting Method neglecting the effect of nonlinear behavior .…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In recent studies, it is observed that the change in the damping of a structure was quite small compared with the stiffness degradation for typical buildings and bridge structures under small excitations . Hence, it can be assumed that the damping matrix is unchanged after the system is damaged when the system remains linearly elastic under small ground excitations . In addition, due to the fact that the damping of a structure may not only relate to the material property of the elements, modeling and updating the damping may introduce significant inaccuracy into the model updating.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al presented a scheme using FRF curvatures to localize damage for a simulated cantilever beam. Recently, several FRF‐based detection methods have been developed by using advanced approaches such as subspace identification algorithms, pattern recognition techniques, orthogonal matching pursuits, and signal processing techniques . The curvature‐based methods seem to be more easily implemented for practical applications in comparison with the many recently proposed approaches …”
Section: Introductionmentioning
confidence: 99%
“…Some are based on the use of frequency response functions (FRFs) as damage-sensitive parameter [17][18][19]; others as the frequency response curvature method and the gapped smoothing method proposed in References [20,21], both define the damage index in terms of the variation of curvature estimated from operational deformed shapes recovered from FRFs. Some are based on the use of frequency response functions (FRFs) as damage-sensitive parameter [17][18][19]; others as the frequency response curvature method and the gapped smoothing method proposed in References [20,21], both define the damage index in terms of the variation of curvature estimated from operational deformed shapes recovered from FRFs.…”
Section: Introductionmentioning
confidence: 99%